Admission control for wireless LANs with multipacket reception capability. Issue 4 (14th August 2013) - Choi, Wooyeol; Lim, Hyuk
Abstract In a multipacket reception (MPR) system, a wireless node can successfully receive multiple packets from simultaneous transmitters. The increase in the number of simultaneous transmissions leads to higher throughput as long as the transmissions can be successfully decoded by the receiver. The maximum number of simultaneous transmissions that the receiver can successfully decode should be determined and used as the criterion of admission control in order to maximise the multipacket reception system performance. In this paper, we propose an admission control scheme that derives the maximum number of simultaneous transmissions and regulates the number of simultaneous transmissions based on the derived number. To evaluate the performance of our proposed scheme, we carry out extensive simulations and show that our proposed scheme significantly improves the network throughput. Copyright © 2013 John Wiley & Sons, Ltd.